Shifting Automotive Landscapes: Privacy and the Right to Travel in the Era of Autonomous Motor Vehicles - Matthew Gillespie (Washington University Journal of Law & Policy, 2016)
This note discusses the changing nature of the right to transportation within the context of the “single-mode” doctrine and consumer privacy laws. Gillespie analyzes how the right to transportation has fundamentally outgrown the United States’ outdated policies, specifically addressing the right to privacy in relation to autonomous motor vehicles (AMVs). Gillespie then argues that the United States should abandon the single-mode transportation doctrine and adopt “comprehensive protections of consumer privacy when information is collected through AMVs.”
Keywords: Transportation; Autonomous Motor Vehicles; AMVs; Consumer privacy; Privacy law; Access to transportation